Usage And Knowledge Of Sunscreen In Politeknik Baubau Students - Dewanti Maisah Ayu; Evi Mustiqawati; Suparman Supardi (International Journal of Multidisciplinary Learners, 2024)
Sunscreen is an important compound to protect the skin from sun exposure, especially ultraviolet (UV) light. Although sunlight plays an important role in life, excessive exposure to UV rays can cause negative impacts, including changes in skin structure, erythema, hyperpigmentation, and premature aging, and contributes about 80% to the development of skin diseases such as aging and skin cancer. This study aims to evaluate the usage behavior and level of knowledge about sunscreen among Baubau Polytechnic students. The research method used was accidental sampling with a total of 68 respondents. The questionnaire distributed was preceded by informed consent which included the name, age, and major of the respondent. The results showed that 4% of respondents had high knowledge about sunscreen, 94% had moderate knowledge, and 1% had low knowledge. In terms of sunscreen use behavior, 30.43% of respondents showed good behavior, 46.37% were good enough, and 23.18% were not good enough. These findings indicate that there are variations in knowledge and behavior of sunscreen use among university students, which need more attention in efforts to increase skin protection awareness and behavior.